Analisis Efektivitas Penyaluran Dana Zakat Melalui Program Banjar Sehat Di Badan Amil Zakat Nasional (BAZNAS) Kabupaten Banjar - Faqih El Wafa; Saputri, Rizki Aulia; Asyahri, Yusuf (EKSISBANK (Ekonomi Syariah dan Bisnis Perbankan), 2023)
Baznas Kabupaten Banjar has been trusted to manage and distribute zakat funds in order to prosper the community which is insufficient in terms of economy. To be able to prosper the community, especially in the field of health services, Baznas must certainly channel its funds effectively. One of the programs initiated by Baznas Banjar Regency is the Banjar Sehat ProgramThis study aims to determine the effectiveness and distribution of zakat funds through the Banjar Sehat program in Baznas, Banjar Regency. The research used is a qualitative research method by taking the type of field research. Data collection method, the authors conducted interviews. It was then analyzed using the effectiveness measure proposed by Sondang P. Siagian. The results of the data analysis concluded that the distribution of zakat funds through the Banjar Sehat program in Baznas, Banjar Regency, was carried out in two ways, namely active and passive stages. As for the effectiveness of the Banjar Sehat program in its distribution, it can does the program to be effective because it has fulfilled all the elements or effectiveness benchmarks stated by Sondang P. Siagian.